Safety and Efficacy of High-intensity Focused Ultrasound Ablation for Patients with Submucosal Fibroids without Fertility Needs: A Single-center Real-world Data Retrospective Study - Xue Shao; Guohua Huang; Yanglu Liu; Hao Zhang; Shuang Luo; Rui Liu (Gynecology and Minimally Invasive Therapy)
Objectives: To analyze clinical outcomes and the factors that influence the therapeutic outcomes of high-intensity focused ultrasound (HIFU) ablation for different types of submucosal uterine fibroids. Materials and Methods: A total of 626 patients without fertility requirements who underwent HIFU ablation for submucosal uterine fibroids at Suining Central Hospital from November 1, 2010, to December 31, 2023, were retrospectively reviewed. The safety and clinical efficacy of HIFU ablation therapy for submucosal uterine fibroids were evaluated. Results: The patients with submucosal uterine fibroids presented increased menstrual volume in 25.24% (158/626) of patients, prolonged menstrual period in 16.93% (106/626) of patients, lower abdominal pain in 5.59% (35/626) of patients, and anemia in 39.46% (247/626) of patients in this study. The average nonperfused volume ratio of type 0, type I, and type II submucosal uterine fibroids was 89.00%, 88.54%, and 85.33%, respectively. No severe adverse events occurred in any of the patients during or after HIFU treatment. Twenty-five patients received reintervention treatment (HIFU or surgical fibroid resection) in 6 months to 7.28 years after HIFU. A significant difference was observed in postoperative combined treatment between the reintervention and non-reintervention group (P < 0.05). Conclusion: HIFU ablation for type 0, type I, and type II submucosal uterine fibroids is safe and effective. The combination management mode after HIFU could reduce the chance of reintervention treatment.